Kepatuhan Wajib Pajak Dalam Implementasi e-Faktur Dengan Pemahaman Internet Sebagai Efek Moderasi - Nandia Ega Pratama; Gideon Setyo Budiwitjaksono (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
Taxpayer compliance is a condition where taxpayers carry out all their tax obligations and rights in formal and material forms. The purpose of this study was to analyze the effect of the Electronic Tax Invoice Application on Corporate Taxpayer Compliance which is moderated by Understanding the Internet. This type of research is descriptive quantitative. The sample in this study was 98 taxable entrepreneurs (PKP) who were active in KPP Pratama Surabaya Rungkut as many as 98 respondents using the calculation of Slovin. The analysis technique in this research is using Partial Least Square analysis. The results of the analysis in this study prove that e-Invoice Reporting has a significant effect on corporate taxpayer compliance. The results of the analysis also prove that understanding of the internet cannot moderate the relationship between e-invoice reporting and corporate taxpayer compliance. Taxable entrepreneur (PKP) at KPP Pratama Surabaya Rungkut complained if they didn’t understand the internet so they came to the KPP Pratama office.